Effects of a probiotic suspension Symprove™ on a rat early-stage Parkinson’s disease model - Sancandi, Marco; De Caro, Carmen; Cypaite, Neringa; Marascio, Nadia; Avagliano, Carmen; De Marco, Carmela; Russo, Emilio; Constanti, Andrew; Mercer, Audrey (Frontiers in Aging Neuroscience, 2023)
An increasing number of studies in recent years have focused on the role that the gut may play in Parkinson’s Disease (PD) pathogenesis, suggesting that the maintenance of a healthy gut may lead to potential treatments of the disease. The health of microbiota has been shown to be directly associated with parameters that play a potential role in PD including gut barrier integrity, immunity, function, metabolism and the correct functioning of the gut-brain axis. The gut microbiota (GM) may therefore be employed as valuable indicators for early diagnosis of PD and potential targets for preventing or treating PD symptoms. Preserving the gut homeostasis using probiotics may therefore lead to a promising treatment strategy due to their known benefits in improving constipation, motor impairments, inflammation, and neurodegeneration. However, the mechanisms underlying the effects of probiotics in PD are yet to be clarified. In this project, we have tested the efficacy of an oral probiotic suspension, SymproveTM, on an established animal model of PD. SymproveTM, unlike many commercially available probiotics, has been shown to be resistant to gastric acidity, improve symptoms in gastrointestinal diseases and improve gut integrity in an in vitro PD model. In this study, we used an early-stage PD rat model to determine the effect of SymproveTM on neurodegeneration and neuroinflammation in the brain and on plasma cytokine levels, GM composition and short chain fatty acid (SCFA) release. SymproveTM was shown to significantly influence both the gut and brain of the PD model. It preserved the gut integrity in the PD model, reduced plasma inflammatory markers and changed microbiota composition. The treatment also prevented the reduction in SCFAs and striatal inflammation, and prevented tyrosine hydroxylase (TH)-positive cell loss by 17% compared to that observed in animals treated with placebo. We conclude that SymproveTM treatment may have a positive influence on the symptomology of early-stage PD with obvious implications for the improvement of gut integrity and possibly delaying/preventing the onset of neuroinflammation and neurodegeneration in human PD patients.